Comparative Analysis of Metaphors in the Economic Context of English and Uzbek Languages - Khayrullayeva Nodira (Researchparks Publishing, 2022)
In linguistics, words are studied in different ways. The semantic aspects of metaphors are so important in the widespread use of metaphors by the speaker. In the language system, lexemes also require each other, they are combined into certain groups based on their specific meanings. This article also discusses the main differences in the category of specific meanings in Uzbek and English economic context.